2013
DOI: 10.1007/s12070-013-0630-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypertension on Hearing

Abstract: To determine the likely association between hypertension and hearing loss. 150 cases and 124 controls, both genders, aged 45-64, included in the research after sample estimation. Hypertension was verified through blood pressure readings and was classified as grade 1, grade 2 and grade 3 hypertension or no hypertension according to the blood pressure readings. Hearing was assessed by measuring pure tone threshold at various frequencies ranging between 250 and 8,000 Hz. There is a significant association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
53
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 15 publications
12
53
3
3
Order By: Relevance
“…(2) All living cells in the human body depend on the adequacy of oxygen and nutrient supply to maintain their function, and that supply depends on the integrity of the structure and function of the heart and blood vessels. Hypertension, the most common vascular disorder that can cause inner ear bleeding, causes progressive or sudden hearing loss (1). Microorganisms in Corti organs can lead to atrophy and reduced hair cells.…”
Section: High Pressure In the Vascular System And Microcirculation Chmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) All living cells in the human body depend on the adequacy of oxygen and nutrient supply to maintain their function, and that supply depends on the integrity of the structure and function of the heart and blood vessels. Hypertension, the most common vascular disorder that can cause inner ear bleeding, causes progressive or sudden hearing loss (1). Microorganisms in Corti organs can lead to atrophy and reduced hair cells.…”
Section: High Pressure In the Vascular System And Microcirculation Chmentioning
confidence: 99%
“…Hypertension is an important health problem because it has a high prevalence and can cause damage to target organs. One of the target organ damage by hypertension is the hearing system that causes hearing loss that can affect the quality of life of a person (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 DM, which is a distinct aetiopathological entity, is more common in older patients, and usually coexists with other health conditions such as hypertension (Tseng, 2006;Comaschi et al, 2005). It has been reported that there is a possible association between hypertension and hearing impairments (Agarwal et al, 2013). Hence, type 2 DM participants were not included in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores sugeriram que os pacientes com HA podem apresentar maior comprometimento auditivo em comparação com indivíduos sem HA (Marková, 1990;Brohem, 1996;Fuess e Cerchiari, 2003;Baraldi, 2004;Marchiori, 2006;Esparza, 2007;Agarwarl et al, 2013).…”
Section: Introductionunclassified